Characterization of the homeless people affected by tuberculosis in Brazil, 2015 to 2021 (Acta Scientiarum. Health Sciences, 2024)
To describe the sociodemographic and clinical-epidemiological profile of homeless people affected by tuberculosis in Brazil, from 2015 to 2021. This is a descriptive, population-based epidemiological study, carried out from the tuberculosis notification records in the Brazilian homeless people, available in the Notifiable Diseases Information System. There was a predominance of male people, of mixed race/color, aged between 30 and 49 years, with (in) complete elementary education and who did not receive social benefits. Regarding the clinical-epidemiological aspects, the type of entry as a new case predominated, with the pulmonary form of the disease, directly observed treatment not performed, with loss of follow-up. The prevalence of alcohol and illicit drug use stands out, in addition to the large number of people who used tobacco. This scenario represents a great challenge, since the presence of tuberculosis prevails in this population, especially as a result of numerous risk factors and situations of vulnerability arising from being homeless. Thus, it is necessary to plan and improve actions that consider the specificities of the group, through inter- and intra-sectoral strategies, focusing on the articulation between public health services and social assistance.